Effect of Porosity on Strength Distribution of Microcrystalline Cellulose - Keleṣ, Özgür (AAPS PharmSciTech, 2015)
Fracture strength of pharmaceutical compacts varies even for nominally identical samples, which directly affects compaction, comminution, and tablet dosage forms. However, the relationships between porosity and mechanical behavior of compacts are not clear. Here, the effects of porosity on fracture strength and fracture statistics of microcrystalline cellulose compacts were investigated through diametral compression tests. Weibull modulus, a key parameter in Weibull statistics, was observed to decrease with increasing porosity from 17 to 56 vol.%, based on eight sets of compacts at different porosity levels, each set containing ∼50 samples, a total of 407 tests. Normal distribution fits better to fracture data for porosity less than 20 vol.%, whereas Weibull distribution is a better fit in the limit of highest porosity. Weibull moduli from 840 unique finite element simulations of isotropic porous materials were compared to experimental Weibull moduli from this research and results on various pharmaceutical materials. Deviations from Weibull statistics are observed. The effect of porosity on fracture strength can be described by a recently proposed micromechanics-based formula.